IMPLEMENTASI METODE KARIMAH DALAM PEMBELAJARAN DAN MENGHAFAL AL QUR’AN DI ICID ( ISLAMIC CENTER I`DADUD DU`AT ) DI PONDOK PESANTREN ISY KARIMA KARANGPANDAN KARANGANYAR JAWA TENGAH - alif bahtiar; Sholihin Sholihin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This research was conducted because of the existence of a da'i educational institution that seeks to participate in helping rural communities who want to learn the basics of Islamic science and preach and apply them in the midst of society. Among the programs are special programs for learning and memorizing the Qur'an. As a supporter of the implementation of the learning program, the teacher provides the karimah method, namely a manual for learning to read the Qur'an and tahsin for beginners in an easy way. Participants are guided to read the standard manuscript of Hafs' history from 'Ashim in accordance with the rules of tajwid which are facilitated through the punctuation marks found in the Rosm 'Uthmani manuscript (international standard Qur'an). The formulation of the problem of this research, first, how is the implementation of the karimah method in learning and memorizing the Qur'an at ICID (Islamic Center I’dadud Du'at) at the Islamic boarding school Isy Karima. Second, what are the supporting and inhibiting factors for the implementation of the karimah method in learning and memorizing the Qur'an at ICID (Islamic Center I`dadud Du`at) at the Islamic boarding school Isy Karima. This type of research is a field research that collects primary data through interviews from the principal and teachers at ICID (Islamic Center I’dadud Du'at) Isy Karima Karanganyar. Secondary data from literature and documents were then analyzed qualitatively, in descriptive form. The results showed that the implementation of the Karimah Method in Learning and Memorizing the Qur'an was very effective for students with the principle of the method in learning referring to